Asymmetric Dimethylarginine as a Surrogate Marker of Endothelial Dysfunction and Cardiovascular Risk in Patients with Systemic Rheumatic Diseases - Dimitroulas, Theodoros (Molecular Diversity Preservation International (MDPI), 2012)
The last few decades have witnessed an increased life expectancy of patients suffering with systemic rheumatic diseases, mainly due to improved management, advanced therapies and preventative measures. However, autoimmune disorders are associated with significantly enhanced cardiovascular morbidity and mortality not fully explained by traditional cardiovascular disease (CVD) risk factors. It has been suggested that interactions between high-grade systemic inflammation and the vasculature lead to endothelial dysfunction and atherosclerosis, which may account for the excess risk for CVD events in this population. Diminished nitric oxide synthesis—due to down regulation of endothelial nitric oxide synthase—appears to play a prominent role in the imbalance between vasoactive factors, the consequent impairment of the endothelial hemostasis and the early development of atherosclerosis. Asymmetric dimethylarginine (ADMA) is one of the most potent endogenous inhibitors of the three isoforms of nitric oxide synthase and it is a newly discovered risk factor in the setting of diseases associated with endothelial dysfunction and adverse cardiovascular events. In the context of systemic inflammatory disorders there is increasing evidence that ADMA contributes to the vascular changes and to endothelial cell abnormalities, as several studies have revealed derangement of nitric oxide/ADMA pathway in different disease subsets. In this article we discuss the role of endothelial dysfunction in patients with rheumatic diseases, with a specific focus on the nitric oxide/ADMA system and we provide an overview on the literature pertaining to ADMA as a surrogate marker of subclinical vascular disease.